Analysis of The Potential of Rancakalong Tourism Using Attraction, Accessibility, Amenity and Ancillary Approaches (4A) - Wasifah Hanim; Hafni Adinda Prasca; Chintya Hermawati; Siti Mardiana; Kralawi Sita (Fakultas Ekonomi Universitas Kadiri, 2023)
Rancakalong District is one of the sub-districts in Sumedang Regency which has various tourist attractions, there as nature tourism, cultural tourism, special food, tourist villages,Ã‚Â and even Sumedang Typical Batik. The Regional Government has established Rancakalong District as a center for natural and cultural tourism destinations. The purpose of this study was to analyze the potential of Rancakalong Tourism as a tourist destination. The analytical method is descriptive qualitative by using a 4 (four) A approach, namely attractions, accessibility, amenities, and ancillary. By using certain criteria, each component is assessed based on 4 (four) classifications, namely low, medium, high,Ã‚Â and very high. The results of the analysis show that the Potential of the Rancakalong District Tourism Area is classified as medium tends to be high